Carbene Radicals in Cobalt(II)–Porphyrin‐Catalysed Carbene Carbonylation Reactions; A Catalytic Approach to Ketenes. Issue 39 (3rd September 2013) - Paul, Nanda D.; Chirila, Andrei; Lu, Hongjian; Zhang, X. Peter; de Bruin, Bas
<x xml:space="preserve">Abstract</x> One‐pot radicals: Cobalt(III)–carbene radicals, generated by metallo‐radical activation of diazo compounds and N‐tosylhydrazone sodium salts with cobalt(II) complexes of porphyrins, readily undergo radical addition to carbon monoxide, allowing the catalytic production of ketenes. These ketenes subsequently react with various amines, alcohols and imines in one‐pot tandem transformations to produce differently substituted amides, esters and β‐lactams in good isolated yields.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>